Galangin Improved Non-Alcoholic Fatty Liver Disease in Mice by Promoting Autophagy - Zhang X; Deng Y; Xiang J; Liu H; Zhang J; Liao J; Chen K; Liu B; Liu J; Pu Y (Drug Design, Development and Therapy, 2020)
Xinxu Zhang, Yuanyuan Deng, Juan Xiang, Huixia Liu, Jiani Zhang, Jie Liao, Ke Chen, Bo Liu, Jun Liu, Ying Pu Department of Geriatric Endocrinology, Xiangya Hospital, Central South University, Changsha, Hunan 410008, People’s Republic of ChinaCorrespondence: Ying PuDepartment of Geriatric Endocrinology, Xiangya Hospital, Central South University, 87 Xiangya Road, Kaifu District, Changsha, Hunan 410008, People’s Republic of ChinaTel +86 137 8727 3373Email puying@mail.csu.edu.cnBackground: Previous studies have shown that curcumin derivatives can improve the fatty degeneration of liver tissue that occurs in nonalcoholic fatty liver disease (NAFLD). However, the specific mechanism for that improvement remains unclear. We examined whether the curcumin derivative galangin could reduce the fatty degeneration of liver tissue in mice with NAFLD by inducing autophagy, from the perspective of both prevention and treatment.Methods: C57BL/6J mice were randomly assigned to a prevention group (given galangin and a HFD simultaneously) or a treatment group (given galangin after being fed an HFD). The prevention group was treated with galangin (100 mg/kg/d) or an equal volume of normal saline (NS) while being fed an HFD. Some mice were treated with an autophagy inhibitor (3-methyladenine, 3-MA; 30 mg/kg/biwk, i.p.) while being fed an HFD and galangin. HepG2 cells were cultured in DMEM medium containing both free fatty acids and galangin.Results: Galangin was found to reduce the fatty degeneration of liver tissue induced by eating an HFD at both the prevention and treatment levels, and that effect might be related to an enhancement of hepatocyte autophagy. Inhibition of autophagy by 3-MA blocked the protective effect of galangin on hepatic steatosis. At the cellular level, galangin reduced lipid accumulation and enhanced the level of hepatocyte autophagy.Conclusion: In vitro and in vivo studies showed that galangin cannot only improve pre-existing hepatic steatosis but also prevent the development of stenosis by promoting hepatocyte autophagy.Keywords: nonalcoholic fatty liver disease, autophagy, galangin, 3-methyladenine, free fatty acid